Synthesis of tinidazole by condensation-oxidation sequence using MoO3/SiO2 bifunctional catalyst - Chandorkar, J. G.; Shubhangi B. Umbarkar; Rode, C. V.; Kotwal, V. B.; Dongare, Mohan K. (Catalysis Communications, 2007)
Antimicrobial drug, tinidazole has been synthesized by condensation of 2-methyl,5-nitro-imidazole and 2-ethyl-thio-ethanol over MoO3/SiO2 catalyst to obtain 1-(2-ethyl-thio-ethanol)-2-methyl-5-nitro-imidazole which is further oxidized using hydrogen peroxide using the same MoO3/SiO2 catalyst to obtain tinidazole. MoO3/SiO2 catalyst (20%), synthesized by sol-gel process showed the highest acid strength and was successfully demonstrated to catalyze both condensation and oxidation in the synthesis of tinidazole. Due to the bifunctional activity of the catalyst, the use of acetic acid for condensation step and tungstic acid or ammonium molybdate for oxidation step in the conventional synthesis of tinidazole could be eliminated, thus making it an environmentally benign process. The catalysts could be recycled five times without any appreciable loss in the conversion and selectivity showing the potential for. the use of MoO3/SiO2 as bifunctional catalyst for the production of this industrially important compound. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: antimicrobial drug; condensation; MoO3/SiO2; Oxidation; solid acid catalyst; tinidazole

Selective hydroxyalkylation of phenol to bisphenol F over dodecatungstophosphoric acid (DTP) impregnated on fumed silica - Garade, Ajit C.; Kshirsagar, V. S.; Rode, C. V. (Applied Catalysis A-General, 2009)
The catalyst activity of various solid acids, such as fumed Silica (SiO(2)) dodecatungstophosphoric acid (DTP), DTP impregnated on SiO(2), amberlyst-15 and montmorillonite KSF/0, was studied for the hydroxyalkylation of phenol to bisphenol F. A well-dispersed DTP on SiO2 catalyst was prepared by the wet impregnation method. The effect of DTP loading on SiO(2) was also compared with bulk DTP and other solid acid catalysts. 20% DTP/SiO(2) catalyst gave the highest products yield of 34.2% and selectivity of 90.1% to bisphenol F, at 353 K and with a phenol-to-formaldehyde mole ratio of 5:1. Ammonia TPD studies of various catalysts showed that an appropriate combination of both strong and weak acid sites of DTP/SiO(2) Was mainly responsible, rather than only the stronger acidity of bulk DTP, for its highest catalytic activity and selectivity. The effect of various reaction parameters like mole ratio, catalyst concentration, temperature and reaction time on product yield and bisphenol F selectivity was also investigated. The catalyst recycle was established by catalyst activity testing. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Bisphenol F; Hydroxyalkylation; NH(3)-TPD; Reaction pathways; solid acid catalysts

Solid acid catalysts: modification of acid sites and effect on activity and selectivity tuning in various reactions - Rode, C. V.; Garade, Ajit C.; Chikate, Rajeev C. (Catalysis Surveys from Asia, 2009)
The effects of acidity and variation in concentration of acid sites of dodecatungstophosphoric acid (DTP), supported DTP and montmorillonite-K catalysts were studied for various organic reactions such as the hydroxyalkylation of phenols to bisphenols, intramolecular rearrangement of benzyl phenyl ether (BPE) to 2-benzyl phenol (2-BP) and selective cleavage of tert-butyldimethylsilyl (TBDMS) ether into the corresponding alcohol. Both dodecatungstophosphoric acid (DTP) impregnated on silica (SiO(2)) and montmorillonite catalysts showed the highest catalyst activity with 90-95% selectivity to bisphenol for the hydroxyalkylation of phenols to give bisphenol. Temperature Programmed Desorption (TPD) of ammonia and activity results of various catalysts showed that an appropriate combination of both strong and weak acidic sites in the catalyst was highly desirable for high bisphenol selectivity. A 10% DTP/SiO(2) catalyst was found to be highly selective for the cleavage of TBDMS ether into the corresponding alcohol at room temperature giving a high TON of 9.5 x 10(5) even after the 4th recycle. DTP was also found to be a promising solid acid catalyst for the intramolecular rearrangement of BPE giving 2-BP.
Keywords: Acidity tuning; Catalytic cleavage; Hydroxyalkylation; Intramolecular rearrangement; solid acid catalysts

Structure-activity studies of dodecatungstophosphoric acid impregnated bentonite clay catalyst in hydroxyalkylation of p-cresol - Garade, Ajit C.; Kshirsagar, V. S.; Jha, Ajay; Rode, C. V. (Catalysis Communications, 2010)
Bentonite clay impregnated with dodecatungstophosphoric acid (20% DTP/BNT) showed an excellent activity, selectivity and stability [95% product yield with 94% selectivity to 2, 2'-methylenebis (4-methylphenol), DAM] for the hydroxyalkylation of p-cresol with formaldehyde at 353 K and for a mole ratio of 5. Ammonia-TPD results showed that an increase in total concentration of acid sites from 4.9 of parent bentonite to 11.6 micromoles per surface area NH(3) (mu molS(-1) NH(3)) of 20% DTP/BNT was due to a strong interaction of protons of bulk DTP with surface hydroxyl groups of BNT as evidenced by (31)P NMR studies. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: (31)P CPMAS NMR; Bentonite; Hydroxyalkylation; p-Cresol; surface modification

Solvent-free carbonylation of glycerol with urea using metal loaded MCM-41 catalysts - Kondawar, S. E.; Potdar, A. S.; Rode, C. V. (RSC Advances, 2015)
Reacting glycerol with urea is the most attractive option for the production of glycerol carbonate (GC) as it utilizes two inexpensive chemicals readily available in the chemical cycle. The overall result is the chemical fixation of carbon dioxide. A Zn/MCM-41(im) catalyst prepared by a wet impregnation method exhibited excellent activity for the reaction of glycerol and urea with 75% glycerol conversion and 98% selectivity to GC. Such excellent activity of the catalyst is explained based on the presence of both basic and acidic sites on the same catalyst which activates the glycerol and urea molecules, respectively.

Selective hydrogenolysis of 5-(hydroxymethyl)furfural over Pd/C catalyst to 2,5-dimethylfuran - Solanki, B. S.; Rode, C. V. (Journal of Saudi Chemical Society, 2019)
everal metal supported catalysts were prepared and evaluated for 5-(hydroxymethyl)furfural (5-HMF) hydrogenolysis to 2,5-dimethylfuran (2,5-DMF) which is a renewable potential fuel additive. Among the prepared catalysts, 3%Pd/C showed excellent performance in terms of complete conversion of 5-HMF along with the highest selectivity of 99% to 2,5-DMF. Detailed physico-chemical characterisation was done in order to understand structure-activity correlation. Uniformly dispersed Pd nanoparticles on activated carbon provided the adsorption surface to enhance the hydrogenation of 5-HMF. Reaction was well optimised and established by extensive study of different reaction parameters like temperature, pressure, reaction time, stirring effect, substrate loading and metal loading.
Keywords: Biomass; Fuel additive; heterogeneous catalysis; Hydrogenolysis; Palladium

Stereoselective aromatic ring hydrogenation over supported rhodium catalysts in supercritical carbon dioxide solvent - Shirai, M.; Hiyoshi, N.; Rode, C. V. (Chemical Record, 2019)
The combination of supported rhodium metal catalysts and supercritical carbon dioxide solvent was effective for the stereoselective ring hydrogenations of aromatic compounds at low temperature. Higher solubility of hydrogen in supercritical carbon dioxide provides higher concentration of hydrogen on the rhodium surface, but lower that of the intermediate on rhodium surface, which suppresses the flipping of surface intermediate, leading to higher catalyst activities and cis selectivities to the corresponding ring-hydrogenated products as compared with those in organic solvents.

Sustainable UV absorbing bio-plastic films by valorisation of humins and chitosan - Lucas, Nishita; Tambe, Snehal S.; Parate, Roopa; Hengne, Amol; Rode, C. V.; Athawale, Anjali A. (International Journal of Biological Macromolecules, 2025)
Humins, an inevitable bio-refinery waste by-product of sugar dehydration have been efficiently utilized for the first time for developing biodegradable thin films for UV shielding. The films were prepared from chitosan, and humins, a novel combination, aiming towards simultaneous utilization of marine and bio-refinery waste, rendering simple, effective, robust UV absorbing films. The structure-activity relationship of these films were elucidated with the help of different analytical techniques like X-ray diffraction, Fourier transform infrared spectroscopy, Thermogravimetric analysis, UV-vis spectroscopy, Atomic force microscopy, Scanning electron microscopy, Tensile testing, Contact angle measurements and water absorption studies. Intrinsic biodegradability was studied using fungi i.e. Aspergillus niger. Different feedstocks (corncob, rice husk, glucose and xylose) were explored for generating humins. Amongst them, humins derived from xylose were utilized for the preparation of the bio-plastic films of chitosan. The results revealed that, addition of 5.0 % humins was observed to be an optimum concentration yielding films with excellent UV absorption, mechanical properties, and biodegradability. The current work is in perfect alignment with sustainability and green chemistry as it ameliorates waste valorization (lignocellulosic and marine altogether). Further, its innovation stems from the first-hand use of humins for UV absorption, novel combination of biopolymers, use of green raw materials.
Keywords: biodegradable; Chitosan; Humins; Thin films; UV absorption; Waste valorization